2014
DOI: 10.3390/en7074588
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Sulfurized Polyacrylonitrile for Superior Performance Lithium/Sulfur Battery

Abstract: Sulfurized polyacrylonitrile (SPAN) is one of the most important sulfurized carbon materials that can potentially be coupled with the carbonaceous anode to fabricate a safe and low cost "all carbon" lithium-ion battery. However, its chemical structure and electrochemical properties have been poorly understood. In this discussion, we analyze the previously published data in combination with our own results to propose a more reasonable chemical structure that consists of short -S x -chains covalently bonded onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
218
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(226 citation statements)
references
References 33 publications
7
218
1
Order By: Relevance
“…75,76 Specifically, the sulfur molecule reacts with PAN to form a heterocyclic polymeric matrix by attaching to the acryl-backbone (Figure 12a), while the sp 3 -hybridzed carbon becomes sp 2 -conjugated with the cyclized nitrile group. 77 The formation of S-S, C-S and C=C bonds is evidenced by FTIR spectroscopy (Figure 12c). 78,79 This structure bypasses the polysulfide shuttle by avoiding the formation of the soluble LiPSs (Li 2 S x , 4 ≤ x ≤ 8).…”
Section: Chemical Bonding Within Polymer Chainsmentioning
confidence: 99%
“…75,76 Specifically, the sulfur molecule reacts with PAN to form a heterocyclic polymeric matrix by attaching to the acryl-backbone (Figure 12a), while the sp 3 -hybridzed carbon becomes sp 2 -conjugated with the cyclized nitrile group. 77 The formation of S-S, C-S and C=C bonds is evidenced by FTIR spectroscopy (Figure 12c). 78,79 This structure bypasses the polysulfide shuttle by avoiding the formation of the soluble LiPSs (Li 2 S x , 4 ≤ x ≤ 8).…”
Section: Chemical Bonding Within Polymer Chainsmentioning
confidence: 99%
“…35 However, the Li 2 S cathode is equally challenging because of its insulating nature and generation of soluble polysulfides upon oxidation, similar to issues with a normal sulfur cathode. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] These issues can be overcome by encapsulating Li 2 S cathodes within electronically conductive carbon-based materials such as graphene and porous carbon. Nevertheless, the use of Li 2 S may not be as appealing for high-energy Li-S cells, (even with Si anodes), because of the loss of active Li toward passivation and also the reduced voltage (∼0.5 V) inherent to the Si anode vs. Li metal.…”
mentioning
confidence: 99%
“…As shown in Figure 1, the double-plateau profiles disappeared after the first lithiation: this is due to the nanoscopic redistribution of sulfur/polysulfides that is a well-known phenomenon among S/PANbased composites (Wang et al, 2002;Yu et al, 2004;Fanous et al, 2011;Doan et al, 2013;Zhang, 2014).…”
Section: Figurementioning
confidence: 96%
“…So far, S/PAN composites show relatively stable cycle life performance even in LiPF 6 /carbonate-based electrolyte solutions (note that any other composites cannot be used in LiPF 6 /carbonate-based electrolyte solutions because of irreversible polysulfides-carbonate reactions) (Wang et al, 2002(Wang et al, , 2003Yu et al, 2004;Fanous et al, 2011;Doan et al, 2013Doan et al, , 2014Zhang et al, 2013d,e;Konarov et al, 2014;Li et al, 2014;Zhang, 2014): it has been explained that the nanoscopic (or sub-nanoscopic) distribution of sulfur/polysulfides in cyclized PAN contributes to the polysulfide stabilization (Wang et al, 2002(Wang et al, , 2003Yu et al, 2004;Fanous et al, 2011;Doan et al, 2013;Zhang, 2014). S/PAN binary composites (Wang et al, 2002) or S/PAN/conducting carbon ternary composites (Wang et al, 2003) were first suggested by Wang et al Recently, S/PAN composites with nanosized additives, such as S/PAN/nanosized Mg 0.6 Ni 0.4 O (MNO) (Zhang et al, 2013d), S/PAN/graphene (Zhang et al, 2013e), and S/PAN/reduced graphene oxide (RGO) , were intensively investigated by the research groups of University of Waterloo (Canada) and Nazarbayev University (Kazakhstan), and it is likely that the use of nanosized filler (either conducting or non-conducting; conducting ones tend to show better rate performance, of course) can contribute to a better cycle life performance than the composites without nanosized fillers probably owing to the more homogeneous sulfur distribution.…”
Section: Introductionmentioning
confidence: 99%